Efektivitas Penggunaan Aplikasi WargaKu dalam Meningkatkan Pelayanan Publik di Kota Surabaya - Adilita, Vara Riya; Rahmawati, Imelda Dian (LANCAH: Jurnal Inovasi dan Tren, 2024)
This study investigates the effectiveness of the "WargaKu" mobile application in enhancing public services in Surabaya. The "WargaKu" app facilitates public complaints and interactions between citizens and the local government. Using a quantitative descriptive method, data were collected through online questionnaires distributed to 40 respondents. The results show that the "WargaKu" app significantly improves service efficiency, transparency, and responsiveness. It enables real-time reporting and tracking of complaints, resulting in quicker resolution and higher citizen satisfaction. The study concludes that the "WargaKu" app effectively enhances public service delivery in Surabaya.